2021
DOI: 10.1089/cap.2021.0010
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Outcomes from Memantine: A Pilot, Double-Blind, Placebo-Controlled Trial in Children with Autism Spectrum Disorder

Abstract: Objective: Studies interrogating therapeutics which alter the excitation-inhibition balance in the treatment of autism spectrum disorder (ASD) have reported mixed results on social and behavioral outcomes. Methods: The aim of this randomized, double-blind placebo-controlled pilot trial was to evaluate neurocognitive effects of memantine over a 24-week trial. Twenty-three children ages 6-12 years old with ASD were randomized to memantine or placebo. Primary outcomes included measures of apraxia and expressive l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…This line of work could, in turn, have important implications for clinical care including improving accuracy of individual prognosis and individualizing treatments in ASD. Recent studies have suggested that memantine might better target cognitive outcomes in ASD rather than social (18). However, the findings from the current study begin to raise the question as to whether social outcomes might still be relevant in an optimally targeted subset of patients.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This line of work could, in turn, have important implications for clinical care including improving accuracy of individual prognosis and individualizing treatments in ASD. Recent studies have suggested that memantine might better target cognitive outcomes in ASD rather than social (18). However, the findings from the current study begin to raise the question as to whether social outcomes might still be relevant in an optimally targeted subset of patients.…”
Section: Discussionmentioning
confidence: 61%
“…Memantine, a moderate affinity N-methyl-D-aspartate (NMDA) glutamate receptor antagonist that attenuates glutamatergic excitation, is an FDA approved treatment for Alzheimer's disease and is known to improve communication abilities in this population (17). A few small studies have shown some effectiveness of memantine in the treatment of social and communication aspects of ASD (18)(19)(20). Considering these cognitive and behavioral outcomes and the impact of memantine on excitatory-inhibitory balance, there has been significant interest in the potential use of memantine to target core symptoms in patients with ASD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent small double-blind trial focusing on neurocognitive measures found a beneficial effect of Memantine on verbal recognition memory and verbal intelligence quotient (VIQ). The authors further hypothesize that Memantine's effect more likely originates from cognitive enhancement than the reduction of behavioral problems [232].…”
Section: Synaptic Plasticity and Excitabilitymentioning
confidence: 96%
“…Although the primary endpoint was not met, exploratory analyses suggested possible clinically significant improvements in core ASD symptoms nonetheless [61]. A small recent RCT (2021) involving 24 participants did not find a difference on primary endpoints related to language and apraxia in ASD but did see some improvement in verbal memory and possibly IQ on secondary and exploratory analyses, although drop-out was high [62]. Additional trials of memantine are under investigation.…”
Section: Agents Targeting Excitatory : Inhibitory Neurotransmissionmentioning
confidence: 98%